An outline economic strategy for Indonesia to sustainably meet its electricity and carbon emissions targets - Les Duckers; Uswatun Hasanah (The Central European Review of Economics and Management (CEREM), 2018)
Aim: ~ In this paper we demonstrate an outline strategy for Indonesia to move its electrical generation from fossil fuels to renewable sources in order to reduce carbon dioxide emissions whilst avoiding excessive costs. The modelling here is based on assumed present fossil fuel generating plants.Design / Research methods:~ We have modelled a representative electrical generation system based on burning coal, oil and gas, and by replacing retiring stations with photovoltaic cells and wind turbines we have considered the cost and carbon dioxide implications over a 30 year period. Additionally the modelling is extended to increasing the Indonesian installed electrical capacity.Conclusions / findings:~ The results show that Indonesia could meet its carbon dioxide emission reduction targets in an economic way by a phased strategy of introducing renewable energy sources. These results are preliminary and will be refined in a future article where we will include the detail of actual existing power stations, with their capacity and anticipated end of life date.Originality / values of the article: There has been, and continues to be, a general resistance to the adoption of renewable energy. This paper shows~ the economic benefit that accompanies carbon dioxide reduction thus presents a new aspect to the consideration of carbon reduction,~Implications of the research:Indonesia faces difficulties in providing electricity whilst meeting its climate change obligations. This research points to a viable economic strategy which may not only meet those obligations, but actually increase electrical provision across the country.Key words: ~Sustainable development, climate change, carbon emissions, renewable energy~JEL: C51,L94,Q01,Q42~Doi:
Keywords: C51; L94; Q01; Q42; 330; Sustainable development; climate change; carbon emissions; renewable energy